Contribution and interaction of visual and vestibular cues for spatial updating in real and virtual environments - Riecke, Bernhard E.; Heyde, M. von der; Bülthoff, H. H (43. Kongress der Deutschen Gesellschaft für Psychologie (DGPS), 2002)
In a series of experiments, we established a speeded pointing paradigm to investigate the influence and interaction of visual and vestibular stimulus parameters for spatial updating in real and virtual environments. STIMULI: Participants saw either the real surround or a photorealistic virtual replica presented via HMD or projection screen. A Stewart motion platform was used for vestibular stimulation. TASK: After simulated or real ego-turns, participants were asked to quickly point towards different previously-learned target objects. Targets were announced consecutively via headphones and chosen to be outside of the current field of view. Performance in real and virtual environments was comparable. Photorealistic visual stimuli from well-known environments including an abundance of salient landmarks proved sufficient to initiate obligatory spatial updating and hence turn the world inside our head, even against our conscious will and without corresponding vestibular cues. Spatial updating benefitted from vestibular cues only when visual turn information was reduced to optic flow information only. There, however, spatial updating was impaired and no longer obligatory. Apart form the well-known smooth spatial updating induced by continuous movement information, we found also a discontinuous, jump-like spatial updating that allowed participants to quickly adopt a new orientation without any explicit motion cues. SUPPORT: Max Planck Society and Deutsche Forschungsgemeinschaft (SFB 550)
Keywords: Riecke; Riecke_2002; bernhard-riecke; conferenceTalksWithoutPaper; iSpaceWeb; markus-von-der-heyde; spatial updating; talkWithoutPaper